In Silico Screening of Small-Molecule Inhibitors for Cancerous Melanoma-Associated Antigen A4 - Otranen, Henna-Riikka (My University, 2026)
Melanoma-Associated Antigen A4 (MAGE-A4) is a cancer-testis antigen expressed in multiple malignancies, and it is associated with more advanced stages and a poor prognosis. To date, no small-molecule ligands targeting MAGE-A4 have been reported. In this study, an in silico–in vitro workflow was utilised to identify small-molecule binders of the melanoma-associated antigen homology domain (MHD) of MAGE-A4. Over 10 million commercially available compounds from four chemical libraries were screened using molecular docking, pose filtering, shape and electrostatic similarity analysis, molecular dynamics simulations, and molecular mechanics/general born surface area binding free energy calculations. Two batches of compounds were selected for experimental validation using microscale thermophoresis. From the first batch of 17 compounds, seven were confirmed to bind MAGE-A4 in vitro. Guided by the binding modes and interaction features of these initial hits, a second batch of 15 compounds was selected using shape-based similarity filtering, yielding 13 validated binders. Several compounds showed low-micromolar affinities, with the most potent compound exhibiting dissociation constants of 3.5 ± 0.3 µM and 3.7 ± 0.5 µM without and with extended incubation, respectively. Most active compounds were predicted to bind a primary cavity within the MHD, engaging conserved acidic and aromatic residues, although a secondary cavity also yielded high-affinity binders. These results demonstrate that MAGE-A4 is targetable with small-molecules, and combining in silico filtering strategies substantially enriches for experimentally confirmed binders. According to current knowledge, the identified compounds are the first reported small-molecule binders of MAGE-A4 and provide a foundation for further optimisation toward therapeutic leads.
Keywords: Melanoma-Associated Antigen A4; Small-Molecule Inhibitors; MAGE-RING E3 Ligase Complex; Computer-Aided Drug Discovery; Microscale Thermophoresis